Low-density, ultra-high-strength and high-entropy alloy and preparation method thereof

By rational ratio CR, AL, V, NB, Ti, MG, and LI elements in high -entropy alloys, and combined with cold -rolled processing and thermal treatment process to prepare low -density ultra -high strong and high -entropy alloys, the existing high entropy is solved The problem of high alloy material density and low -quality high -entropy alloy material strength realizes the low density, high strength and good stretching of alloy.

CN119082585BActive Publication Date: 2025-01-28CHINALCO MATERIALS APPL RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411590674.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-28
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The high density of existing high entropy alloy materials limits their use in engineering applications. At the same time, lightweight high entropy alloy materials usually exhibit low strength or low plasticity, which is difficult to match high strength and good tensile plasticity.

Method used

Through a reasonable ratio CR, Al, V, NB, Ti, MG, and LI elements, combined with cold -rolled processing and thermal treatment technology, to prepare low -density, high -tough and high -entropy alloys. The composition of the alloy includes CR: 5 ~ 10%, Al: 10 ~ 20%, V: 10 ~ 20%, NB: 5 ~ 10%, TI: 30 ~ 60%, Mg: 0 to 10%, li: 0 ~ 5%.

Benefits of technology

The low -density of alloy (less than 5 G/CM³), high -tensile strength (≥1 GPA) and good extension (≥15%) have extensive application potential, especially in the fields of aerospace and automobile manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119082585B_ABST
    Figure CN119082585B_ABST
Patent Text Reader

Abstract

The present invention provides a low-density, ultra-high strength and toughness high-entropy alloy and a preparation method thereof. The low-density, ultra-high strength and toughness high-entropy alloy comprises the following components: in atomic percentage, Cr: 5-10%, Al: 10-20%, V: 10-20%, Nb: 5-10%, Ti: 30-60%, Mg: 0-10%, Li: 0-5%. The low-density, ultra-high strength and toughness high-entropy alloy of the present invention has lower density, higher strength and better toughness than similar materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to a low-density ultra-high-strength high-entropy alloy and a preparation method thereof. Background Art

[0002] High entropy alloys have unique properties that cannot be matched by traditional alloys due to their unique atomic structure characteristics. They show unique advantages in physical, chemical and thermodynamic properties, and their fracture toughness and elastic modulus are significantly higher than those of traditional alloys. However, most of the systems studied so far are based on FCC structure high entropy alloys composed of transition elements and BCC structure high entropy alloys composed of refractory elements. Since the density of the elements selected for these alloys is generally large, the density of the prepared high entropy alloys is relatively high (greater than 8 g·cm -3 ), which limits its practical engineering application.

[0003] The lightweight high entropy alloy system currently studied is mainly based on light elements for alloy design. According to the composition elements and content, the designed alloy density is mainly distributed in 1.5 g cm -3 (such as Al-Mg-Li based alloys) to 6.5 g·cm -3 (such as Ti-V-Zr-Nb-based alloys). However, due to the large atomic radius difference between the components and the low mixing enthalpy of the composition system, these lightweight high-entropy alloys usually contain a large number of brittle precipitates (such as intermetallic compounds and ordered phases), which usually show low strength or low plasticity. The density of lightweight high-entropy alloys composed of light elements such as Al, Li, Mg, Ca, Zn, Sn, Si and Cu usually does not exceed 4.5 g cm -3 , but its strength generally does not exceed 500 MPa. Low-density refractory high-entropy alloys (such as Al-Nb-Ti-V-Zr and Cr-Nb-Ti-V-Zr) show high room-temperature compressive strength, but the alloys have almost no tensile plasticity, which greatly limits the application scope of lightweight high-entropy alloys. Based on this, it is necessary to develop a lightweight high-entropy alloy material with both high strength and sufficient tensile plasticity.

[0004] Therefore, it is necessary to provide a high-entropy alloy material with low density and high toughness to solve the above-mentioned problems existing in traditional materials. Summary of the invention

[0005] The main purpose of the present invention is to provide a low-density ultra-high strength and toughness high-entropy alloy and a preparation method thereof, so as to solve the problems of low density, high strength and difficult matching of tensile plasticity of high-entropy alloys in the prior art.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a low-density, ultra-high-strength and high-entropy alloy, which comprises the following components: in atomic percentage, Cr: 5-10%, Al: 10-20%, V: 10-20%, Nb: 5-10%, Ti: 30-60%, Mg: 0-10%, and Li: 0-5%.

[0007] In the alloy of the present invention, the Cr element improves the strength of the material through solid solution strengthening, and can improve the corrosion resistance of the alloy. The Cr content will affect the phase stability of the alloy, thereby affecting the microstructure and performance of the material. In terms of atomic percentage, the Cr content of the present invention is 5-10%, preferably 5-8%. If the Cr content is lower than this range, it may not be enough to provide sufficient strengthening effect, and the corrosion resistance may also be affected. If the Cr content is higher than this range, the phase stability of the alloy may change, forming a multiphase structure that is not conducive to the performance of the material, or in some cases may cause embrittlement of the material.

[0008] The Al element can improve the hardness, strength and wear resistance of the alloy, and can improve its high temperature oxidation resistance. In terms of atomic percentage, the Al content of the present invention is 10-20%, preferably 13-20%. If the Al content is lower than this range, the above-mentioned strengthening effect may not be fully exerted, and the hardness, wear resistance and high temperature oxidation resistance of the alloy may be affected. If the Al content is higher than this range, alloy compounds may be generated, which may reduce the plasticity of the alloy.

[0009] The V element can significantly improve the tensile strength and yield strength of the alloy. In terms of atomic percentage, the V content of the present invention is 10-20%, preferably 12-20%. If the V content is lower than this range, the above-mentioned strengthening effect may not be fully exerted, and the hardness and strength of the alloy may be affected. If the V content is higher than this range, it may cause adverse changes in the phase structure of the alloy, such as forming a multiphase structure that is not conducive to material performance, or may cause embrittlement of the material in some cases.

[0010] The Nb element can improve the strength and hardness of the alloy, and the Nb content will affect the structural stability of the alloy, thereby affecting the microstructure and performance of the material. In terms of atomic percentage, the Nb content of the present invention is 5-10%, preferably 8-10%. If the Nb content exceeds this range, the above-mentioned strengthening effect may not be fully exerted, and the hardness, strength, heat resistance and corrosion resistance of the alloy may be affected.

[0011] The Ti element can appropriately improve the mechanical stability, reduce its ability to resist fracture, and affect its toughness. Moreover, the addition of the Ti element will cause the lattice constant to increase, while the density will decrease accordingly. In terms of atomic percentage, the content of Ti in the present invention is 30-60%, preferably 40-60%, and more preferably 43-60%. If the content of Ti is lower than this range, the above-mentioned strengthening effect may not be fully exerted, and the hardness and strength of the alloy may be affected. If the content of Ti is higher than this range, it may cause adverse changes in the phase structure of the alloy, such as forming a multiphase structure that is not conducive to the performance of the material, or may cause embrittlement of the material in some cases. In addition, too high a Ti content may affect the density and porosity of the alloy, resulting in a decrease in the density of the alloy and an increase in the porosity, thereby affecting the mechanical properties of the material.

[0012] Mg and Li are light elements that can reduce the density of the alloy. The addition of Mg can increase the specific strength of the alloy and can affect the microstructure of the high entropy alloy, including the lattice type and phase composition. The addition of Li can improve the electrochemical properties of the alloy and can affect the microstructure of the high entropy alloy, including the grain size and phase composition. In terms of atomic percentage, the content of Mg in the present invention is 0 to 10%, preferably 0 to 5%, and more preferably 0 to 1%; the content of Li is 0 to 5%, preferably 0 to 2%, and more preferably 0 to 0.5%.

[0013] It should be noted that in high entropy alloys, the corresponding effects cannot be achieved by arbitrarily adjusting the element content. The specific effects and influences will also be affected by the types and contents of other alloying elements. The interactions between the various elements in high entropy alloys are complex and difficult to predict. The physicochemical properties of each element, such as atomic radius, electronegativity, lattice parameters, etc., will affect the final performance of the alloy. The stability of its structure involves complex thermodynamic and kinetic factors, which need to be predicted and verified by calculation and experiment. Although the multi-principal element design concept of high entropy alloys has increased the freedom of composition selection and performance regulation, it has also greatly increased the difficulty of alloy optimization design. Traditional empirical trial and error methods, thermodynamic simulations, first-principles calculations and other methods have obvious shortcomings in guiding the composition design of high entropy alloys.

[0014] The inventors obtained the technical solution of the present invention through a lot of creative work and a lot of experiments. The inventors surprisingly found that the high entropy alloy material of the present invention has both low density and high toughness.

[0015] Preferably, the alloy of the present invention consists of the following components: in atomic percentage, Cr: 5-10%, Al: 10-20%, V: 10-20%, Nb: 5-10%, Ti: 30-60%, Mg: 0-10%, Li: 0-5%.

[0016] When the alloy of the present invention is basically composed of the above alloy and uses the above ratio, it exhibits excellent mechanical properties, such as high strength, high toughness and good ductility. These properties make the alloy have a wide range of application potentials in the fields of aerospace, automobile manufacturing, energy industry and medical equipment. Due to its low density characteristics, the alloy also helps to reduce the weight of the structure, thereby improving energy efficiency and performance.

[0017] More preferably, the alloy of the present invention consists of the following components: in atomic percentage, Cr: 5-8%, Al: 13-20%, V: 12-20%, Nb: 8-10%, Ti: 40-60%, Mg: 0-5%, Li: 0-2%.

[0018] The present inventors have found that adjusting the component contents within the above ranges can further improve mechanical properties such as tensile strength and elongation.

[0019] Most preferably, the alloy of the present invention consists of the following components: in atomic percentage, Cr: 5-8%, Al: 13-20%, V: 12-20%, Nb: 8-10%, Ti: 43-60%, Mg: 0-1%, Li: 0-0.5%.

[0020] In the present invention, by further accurately controlling the proportions of elements such as Cr, Al, V, Nb, Ti, Mg and Li, an optimized design of the alloy is achieved to obtain the best mechanical properties.

[0021] Furthermore, the density of the alloy of the present invention is less than 5 g / cm 3 .

[0022] The low-density, ultra-high-strength and high-entropy alloy of the present invention has a density of less than 5 g / cm³, which gives it a significant advantage in lightweight applications. The weight of the structure can be reduced without sacrificing strength and toughness, thereby improving energy efficiency and performance. This is particularly important for fields such as aerospace, automotive manufacturing, and portable electronic devices, as these fields have strict requirements for lightweight and high performance of materials. In addition, low density also helps to reduce material costs and improve production efficiency because less material is used to achieve the required mechanical properties.

[0023] Furthermore, the alloy of the present invention has a tensile strength of ≥1 GPa and an elongation of ≥15%.

[0024] The low-density, ultra-high-toughness high-entropy alloy of the present invention has significant mechanical property advantages, and its tensile strength is as high as 1GPa, which means that the alloy exhibits extremely high strength and stability when subjected to tensile force, and can effectively resist deformation and fracture. At the same time, the elongation ≥15% indicates that the alloy has good plasticity during the stretching process and can deform to a certain extent without breaking, which helps to absorb and disperse stress and improve the toughness of the material. The tensile strength and elongation can be measured in accordance with GB / T 228.2-2015. This combination of excellent strength and toughness makes the alloy have broad application prospects in the fields of aerospace, automobile manufacturing, etc., especially in situations where lightweight and high-strength structural components are required.

[0025] According to another aspect of the present invention, there is provided a method for preparing a low-density ultra-high-strength high-entropy alloy, the method comprising the following steps:

[0026] Step S1, pre-treating the metal raw material;

[0027] Step S2, stacking and smelting the metal raw materials in order of melting points;

[0028] Step S3, after smelting evenly, cooling to obtain a lightweight ultra-high strength and toughness high entropy alloy ingot;

[0029] Step S4, cold rolling the alloy ingot;

[0030] Step S5, heat treating the alloy cold-rolled sheet obtained in step S4 to obtain a low-density, ultra-high-strength, high-entropy alloy.

[0031] Preferably, the chemical purity of the metals of the present invention is above 99.9 wt %.

[0032] In alloys, the presence of impurities is usually unavoidable, and even in high-purity alloys, there are trace amounts of other elements. For example, the raw materials of the alloy may contain a certain amount of impurities, which are difficult to completely remove during the smelting process; during the smelting and casting process, the alloy may absorb impurities from the materials it contacts. It should be understood that even if the alloy of the present invention limits the component content to 100%, it can still contain impurities at a normal content. Preferably, the alloy of the present invention contains as low an impurity content as possible, and even ideally contains no impurities.

[0033] The high chemical purity of metals will help improve the performance and stability of alloys. High-purity metal alloys generally have better mechanical properties, such as strength, hardness and ductility, while reducing the brittleness of the material and improving corrosion resistance and oxidation resistance. In addition, high-purity metal alloys are easier to form and weld during processing, which helps to improve production efficiency and reduce costs.

[0034] More specifically, in step S1, the pretreatment may optionally include the following aspects: preparing raw materials according to the required ratio of the high entropy alloy; removing oil stains, oxide layers or other impurities that may exist on the surface of the raw materials through cleaning treatment; and performing drying treatment before smelting.

[0035] In step S2, smelting is performed in a vacuum environment, preferably in a vacuum arc furnace. Each component is placed according to the melting point to ensure the uniformity of smelting. After cooling, smelting is repeated 6-7 times.

[0036] In step S3, a vacuum suction casting device is used to suction cast the alloy obtained in step S2 into a water-cooled copper mold to obtain a lightweight, ultra-high-strength, high-entropy alloy ingot; wherein the vacuum degree reaches 5×10 -3 Pa, and rapidly cooled to room temperature at a rate of more than 1500°C / s;

[0037] In step S4, the deformation of a single pass of cold rolling is about 5-10%, and the total deformation is 70-95%;

[0038] In step S5, the alloy cold-rolled sheet obtained in step S4 is heat-treated at 600-800°C for 1-5 hours.

[0039] Preferably, the preparation method of the present invention comprises the following steps:

[0040] Step S1, removing the surface oxide film of Cr, Al, V, Nb, Ti, Mg, and Li metal raw materials, and designing the distribution ratio according to the above-mentioned alloy composition;

[0041] Step S2, stacking the raw materials in a vacuum arc furnace in order of melting point, starting smelting, and smelting again after the alloy ingot cools down, repeating the smelting 6-7 times;

[0042] Step S3, after the alloy is fully and evenly melted, the alloy is sucked into a water-cooled copper mold using a vacuum suction casting device to obtain a low-density, ultra-high-strength, high-entropy alloy ingot;

[0043] Step S4, cold rolling the alloy ingot, with a single-pass deformation of about 5-10% and a total deformation of 75-95%;

[0044] Step S5, heat treatment is performed on the alloy cold-rolled sheet obtained in step S4 at 650-800°C for 1-5 hours to obtain a low-density, ultra-high-strength, high-entropy alloy.

[0045] Cold rolling deformation can effectively reduce grain size, improve tensile strength and elongation, but insufficient deformation will result in unsatisfactory strengthening effect; reasonable annealing treatment can eliminate deformation stress and improve elongation. Too low temperature makes it difficult to eliminate stress, and too high temperature will cause unnecessary precipitation phases to appear, resulting in reduced toughness.

[0046] By applying the technical solution of the present invention, a high entropy alloy material with low density, high strength and tensile plasticity is obtained by adjusting the reasonable ratio of Cr, Al, V, Nb, Ti, Mg and Li and combining the corresponding cold deformation and heat treatment processes. The density of the alloy is less than 5 g / cm 3 , tensile strength ≥1 GPa, and elongation ≥15%.

[0047] The alloy of the present invention can be applied to, for example, component structural materials in the aerospace field, such as aircraft engines and spacecraft; medical equipment materials, such as dental implants and surgical knives; component materials for high-performance electronic equipment; materials for the nuclear energy industry, such as nuclear fuel cladding and high-pressure vessels; and lightweight applications in the preparation of mobile device casings, battery negative electrode materials, and the transportation industry.

[0048] In summary, the low-density ultra-high strength and toughness high-entropy alloy of the present invention has lower density, higher strength and better toughness compared with the same type of materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The drawings in the specification, which constitute a part of this application, are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0050] Figure 1 The SEM photograph of the lightweight, ultra-high strength and toughness high entropy alloy prepared in Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0051] The present application is further described in detail below in conjunction with examples. These examples are intended to better further understand the present invention, are not limited to the best mode of implementation, and do not limit the content and protection scope of the present invention. Any product that is the same or similar to the present invention and is obtained by anyone under the inspiration of the present invention or by combining the present invention with the features of other prior arts falls within the protection scope of the present invention.

[0052] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The experimental methods used in the following embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial sources.

[0053] Comparative Example 1

[0054] Lightweight high entropy alloy, atomic percentage: Al: 66%, Cu: 6%, Mg: 22%, Si: 1%, Zn: 5%.

[0055] The specific steps of preparation are:

[0056] 1) Grind the surface of Al, Cu, Mg, Si, and Zn raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0057] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 7 times.

[0058] 3) After the alloy is fully melted and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight high-entropy alloy ingot.

[0059] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 2% and a total deformation of 10%.

[0060] 5) The alloy cold-rolled sheet was heat treated at 350°C for 1 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0061] The density of the obtained alloy is 2.85 g / cm 3 , the obtained Al66Mg22Cu6Zn5Si1 alloy has tensile brittle characteristics and the tensile strength cannot be obtained (see Table 1).

[0062] Comparative Example 2

[0063] Lightweight high entropy alloy, in atomic percentage: Al: 25%, V: 25%, Nb: 25%, Ti: 25%.

[0064] The specific steps of preparation are:

[0065] 1) Grind the surface of Al, V, Nb, and Ti metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0066] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 7 times.

[0067] 3) After the alloy is fully melted and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight high-entropy alloy ingot.

[0068] 4) Alloy ingots cannot be further cold rolled.

[0069] The density of the obtained AlVNbTi alloy is 5.49 g / cm 3 The obtained AlVNbTi alloy has tensile brittle characteristics and cannot obtain tensile strength (see Table 1).

[0070] Example 1

[0071] Low-density, ultra-high-strength and high-entropy alloy, in atomic percentage: Cr: 5%, Al: 13%, V: 12%, Nb: 9%, Ti: 60%, Mg: 0.5%, Li: 0.5%.

[0072] The specific steps of preparation are:

[0073] 1) Grind the surface of Cr, Al, V, Nb, Ti, Mg, and Li metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0074] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 7 times.

[0075] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0076] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 5% and a total deformation of 85%.

[0077] 5) The alloy cold-rolled sheet was heat treated at 750°C for 1 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0078] The density of the obtained Cr5Al12V12Nb10Ti60Mg0.5Li0.5 alloy is 4.87 g / cm 3 (See Table 1), the tensile strength of the obtained Cr5Al12V12Nb10Ti60Mg0.5Li0.5 alloy is 1032MPa and the elongation is 17% (See Table 1); the SEM photo of the alloy is shown in Figure 1 shown.

[0079] Example 2

[0080] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 8%, Al: 14%, V: 15%, Nb: 8%, Ti: 54%, Mg: 1%.

[0081] The specific steps of preparation are:

[0082] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0083] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 7 times.

[0084] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0085] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 10% and a total deformation of 90%.

[0086] 5) The alloy cold-rolled sheet was heat treated at 600°C for 5 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0087] The density of the obtained Cr8Al14V15Nb8Ti54Mg1 alloy is 4.92 g / cm 3 The obtained Cr8Al14V15Nb8Ti54Mg1 alloy has a tensile strength of 1100 MPa and an elongation of 16% (see Table 1).

[0088] Example 3

[0089] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 7%, Al: 19.5%, V: 20%, Nb: 10%, Ti: 43%, Li: 0.5%.

[0090] The specific steps of preparation are:

[0091] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Li metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0092] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is melted again and the smelting is repeated 6 times.

[0093] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0094] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 8% and a total deformation of 95%.

[0095] 5) The alloy cold-rolled sheet was heat treated at 800°C for 1 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0096] The density of the obtained Cr7Al19.5V20Nb10Ti43Li0.5 alloy is 4.97 g / cm 3The obtained Cr7Al19.5V20Nb10Ti43Li0.5 alloy has a tensile strength of 1120 MPa and an elongation of 15% (see Table 1).

[0097] Example 4

[0098] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 6%, Al: 14%, V: 15%, Nb: 9%, Ti: 55%, Mg: 1%.

[0099] The specific steps of preparation are:

[0100] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0101] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is melted again and the smelting is repeated 6 times.

[0102] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0103] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 10% and a total deformation of 90%.

[0104] 5) The alloy cold-rolled sheet was heat treated at 700°C for 2 h to obtain a lightweight, ultra-high strength and toughness high-entropy alloy.

[0105] The density of the obtained Cr6Al14V15Nb9Ti55Mg1 alloy is 4.92 g / cm 3 The obtained Cr6Al14V15Nb9Ti55Mg1 alloy has a tensile strength of 1051 MPa and an elongation of 16% (see Table 1).

[0106] Embodiment 5:

[0107] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 10%, Al: 14%, V: 15%, Nb: 8%, Ti: 52%, Mg: 1%.

[0108] The specific steps of preparation are:

[0109] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0110] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is melted again and the smelting is repeated 7 times.

[0111] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0112] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 8% and a total deformation of 80%.

[0113] 5) The alloy cold-rolled sheet was heat treated at 650°C for 4 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0114] The density of the obtained Cr10Al14V15Nb8Ti52Mg1 alloy is 4.96 g / cm 3 The obtained Cr10Al14V15Nb8Ti52Mg1 alloy has a tensile strength of 1105 MPa and an elongation of 15% (see Table 2).

[0115] Embodiment 6:

[0116] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 8%, Al: 10%, V: 15%, Nb: 8%, Ti: 58%, Mg: 1%.

[0117] The specific steps of preparation are:

[0118] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0119] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is melted again and the smelting is repeated 7 times.

[0120] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0121] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 10% and a total deformation of 90%.

[0122] 5) The alloy cold-rolled sheet was heat treated at 700°C for 3 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0123] The density of the obtained Cr8Al10V15Nb8Ti58Mg1 alloy is 4.99 g / cm 3The obtained Cr8Al10V15Nb8Ti58Mg1 alloy has a tensile strength of 1050 MPa and an elongation of 17% (see Table 2).

[0124] Embodiment 7:

[0125] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 8%, Al: 14%, V: 10%, Nb: 8%, Ti: 59%, Mg: 1%.

[0126] The specific steps of preparation are:

[0127] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0128] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 7 times.

[0129] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0130] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 5% and a total deformation of 75%.

[0131] 5) The alloy cold-rolled sheet was heat treated at 750°C for 2 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0132] The density of the obtained Cr8Al14V10Nb8Ti59Mg1 alloy is 4.85 g / cm 3 The obtained Cr8Al14V10Nb8Ti59Mg1 alloy has a tensile strength of 1080 MPa and an elongation of 16% (see Table 2).

[0133] Embodiment 8:

[0134] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 8%, Al: 14%, V: 15%, Nb: 5%, Ti: 57%, Mg: 1%.

[0135] The specific steps of preparation are:

[0136] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0137] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 7 times.

[0138] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0139] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 5% and a total deformation of 70%.

[0140] 5) The alloy cold-rolled sheet is heat treated at 800°C for 2 hours to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0141] The density of the obtained Cr8Al14V15Nb5Ti57Mg1 alloy is 4.79 g / cm 3 The obtained Cr8Al14V15Nb5Ti57Mg1 alloy has a tensile strength of 1075 MPa and an elongation of 15% (see Table 2).

[0142] Comparative Example 3:

[0143] Lightweight high entropy alloy, in atomic percentage: Cr: 7%, Al: 21%, V: 20%, Nb: 10%, Ti: 41.5%, Li: 0.5%.

[0144] The specific steps of preparation are:

[0145] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Li metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0146] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 6 times.

[0147] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0148] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 8% and a total deformation of 95%.

[0149] 5) The alloy cold-rolled sheet was heat treated at 800°C for 1 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0150] The density of the obtained Cr7Al21V20Nb10Ti41.5Li0.5 alloy is 4.95 g / cm 3The obtained Cr7Al21V20Nb10Ti41.5Li0.5 alloy has a tensile strength of 1107 MPa and an elongation of 12% (see Table 3).

[0151] Comparative Example 4:

[0152] Lightweight high entropy alloy, in atomic percentage: Cr: 4%, Al: 12%, V: 12%, Nb: 10%, Ti: 61%, Mg: 0.5%, Li: 0.5%.

[0153] The specific steps of preparation are:

[0154] 1) Grind the surface of Cr, Al, V, Nb, Ti, Mg, and Li metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0155] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 7 times.

[0156] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0157] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 5% and a total deformation of 85%.

[0158] 5) The alloy cold-rolled sheet was heat treated at 750°C for 1 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0159] The density of the obtained Cr4Al12V12Nb10Ti61Mg0.5Li0.5 alloy is 4.91 g / cm 3 (See Table 1), the tensile strength of the obtained Cr4Al12V12Nb10Ti61Mg0.5Li0.5 alloy is 980MPa and the elongation is 17% (See Table 3).

[0160] Comparative Example 5:

[0161] Lightweight high entropy alloy, in atomic percentage: Cr: 7%, Al: 19.5%, V: 21%, Nb: 10%, Ti: 42%, Li: 0.5%.

[0162] The specific steps of preparation are:

[0163] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Li metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0164] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is melted again and the smelting is repeated 6 times.

[0165] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0166] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 8% and a total deformation of 95%.

[0167] 5) The alloy cold-rolled sheet was heat treated at 800°C for 1 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0168] The density of the obtained Cr7Al19.5V21Nb10Ti42Li0.5 alloy is 4.99 g / cm 3 The obtained Cr7Al19.5V21Nb10Ti42Li0.5 alloy has a tensile strength of 1103 MPa and an elongation of 11% (see Table 3).

[0169] Comparative Example 6:

[0170] Lightweight high entropy alloy, in atomic percentage: Cr: 5%, Al: 12%, V: 12%, Nb: 11%, Ti: 59%, Mg: 0.5%, Li: 0.5%.

[0171] The specific steps of preparation are:

[0172] 1) Grind the surface of Cr, Al, V, Nb, Ti, Mg, and Li metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0173] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is melted again and the smelting is repeated 7 times.

[0174] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0175] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 5% and a total deformation of 85%.

[0176] 5) The alloy cold-rolled sheet was heat treated at 750°C for 1 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0177] The density of the obtained Cr5Al12V12Nb11Ti59Mg0.5Li0.5 alloy is 4.97 g / cm 3 (See Table 1), the tensile strength of the obtained Cr5Al12V12Nb11Ti59Mg0.5Li0.5 alloy is 988MPa and the elongation is 17% (See Table 3).

[0178] Comparative Example 7:

[0179] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 6%, Al: 14%, V: 15%, Nb: 9%, Ti: 55%, Mg: 1%.

[0180] The specific steps of preparation are:

[0181] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0182] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 6 times.

[0183] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0184] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 10% and a total deformation of 50%.

[0185] 5) The alloy cold-rolled sheet was heat treated at 700°C for 2 h to obtain a lightweight, ultra-high strength and toughness high-entropy alloy.

[0186] The density of the obtained Cr6Al14V15Nb9Ti55Mg1 alloy is 4.92 g / cm 3 The obtained Cr6Al14V15Nb9Ti55Mg1 alloy has a tensile strength of 821 MPa and an elongation of 10% (see Table 3).

[0187] Comparative Example 8:

[0188] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 6%, Al: 14%, V: 15%, Nb: 9%, Ti: 55%, Mg: 1%.

[0189] The specific steps of preparation are:

[0190] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0191] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 6 times.

[0192] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0193] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 10% and a total deformation of 90%.

[0194] 5) The alloy cold-rolled sheet was heat treated at 500°C for 2 h to obtain a lightweight, ultra-high strength and toughness high entropy alloy.

[0195] The density of the obtained Cr6Al14V15Nb9Ti55Mg1 alloy is 4.92 g / cm 3 The obtained Cr6Al14V15Nb9Ti55Mg1 alloy has a tensile strength of 1130 MPa and an elongation of 7% (see Table 3).

[0196] Comparative Example 9:

[0197] Low-density, ultra-high-strength and high-entropy alloy, atomic percentage: Cr: 6%, Al: 14%, V: 15%, Nb: 9%, Ti: 55%, Mg: 1%.

[0198] The specific steps of preparation are:

[0199] 1) Grind the surface of Cr, Al, V, Nb, Ti, and Mg metal raw materials to remove the surface oxide film. Design the distribution ratio according to the above alloy composition.

[0200] 2) The raw materials are stacked in the vacuum arc furnace in order of melting point and smelting begins. After the alloy ingot cools down, it is smelted again and the smelting is repeated 6 times.

[0201] 3) After the alloy is fully and evenly melted, use vacuum suction casting equipment to suck the alloy into a water-cooled copper mold and quickly cool it to room temperature at a rate of about 1500°C / s to obtain a lightweight, ultra-high-strength and tough high-entropy alloy ingot.

[0202] 4) The alloy ingot is cold rolled, with a single-pass deformation of about 10% and a total deformation of 90%.

[0203] 5) The alloy cold-rolled sheet was heat treated at 700°C for 8 h to obtain a lightweight, ultra-high strength and toughness high-entropy alloy.

[0204] The density of the obtained Cr6Al14V15Nb9Ti55Mg1 alloy is 4.92 g / cm 3 The obtained Cr6Al14V15Nb9Ti55Mg1 alloy has a tensile strength of 912 MPa and an elongation of 16% (see Table 3).

[0205] The following Table 1 shows the density, phase composition and mechanical property data obtained for Comparative Examples 1 to 2 and Examples 1 to 4; Table 2 shows the density, phase composition and mechanical property data obtained for Examples 5 to 8; Table 3 shows the density, phase composition and mechanical property data obtained for Comparative Examples 3 to 9.

[0206] Table 1

[0207]

[0208] Table 2

[0209]

[0210] Table 3

[0211]

[0212] By comparing the above Examples 1 to 8 and Comparative Examples 1 to 9, it can be seen that the low-density ultra-high strength and toughness high-entropy alloy of the present invention has lower density, higher strength and better toughness than the comparative examples.

[0213] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low-density, ultra-high-strength, high-entropy alloy, characterized in that: The alloy comprises the following components: in atomic percentage, Cr: 5-10%, Al: 10-20%, V: 10-20%, Nb: 8-10%, Ti: 40-60%, Mg: 0-10%, Li: 0-5%, and the density of the alloy is less than 5 g / cm 3 .

2. The alloy according to claim 1, characterized in that The alloy consists of the following components: in atomic percentage, Cr: 5-10%, Al: 10-20%, V: 10-20%, Nb: 8-10%, Ti: 40-60%, Mg: 0-10%, and Li: 0-5%.

3. The alloy according to claim 1, characterized in that The alloy consists of the following components: in atomic percentage, Cr: 5-8%, Al: 13-20%, V: 12-20%, Nb: 8-10%, Ti: 40-60%, Mg: 0-5%, and Li: 0-2%.

4. The alloy according to claim 1, characterized in that The alloy consists of the following components: in atomic percentage, Cr: 5-8%, Al: 13-20%, V: 12-20%, Nb: 8-10%, Ti: 43-60%, Mg: 0-1%, and Li: 0-0.5%.

5. The alloy according to any one of claims 1 to 4, characterized in that The tensile strength of the alloy is ≥1 GPa, and the elongation is ≥15%.

6. The method for preparing a low-density, ultra-high-toughness, high-entropy alloy according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: Step S1, pre-treating the metal raw material; Step S2, stacking and smelting the metal raw materials in order of melting points; Step S3, after being evenly smelted, cooling to obtain a lightweight, ultra-high strength and toughness high entropy alloy ingot; Step S4, cold rolling the alloy ingot; Step S5, heat treating the alloy cold-rolled sheet obtained in step S4 to obtain the low-density ultra-high-strength and high-entropy alloy.

7. The preparation method according to claim 6, characterized in that: The chemical purity of the metals is above 99.9 wt %.

8. The preparation method according to claim 6 or 7, characterized in that: In step S2, the alloy is cooled and then melted again, and the melting is repeated 6-7 times; in step S3, a vacuum suction casting device is used to suck the alloy obtained in step S2 into a water-cooled copper mold to obtain the lightweight ultra-high strength and toughness high entropy alloy ingot; in step S4, the single-pass deformation amount of the cold rolling process is 5-10%, and the total deformation amount is 70-95%; and / or in step S5, the alloy cold-rolled sheet obtained in step S4 is subjected to a heat treatment at 600-800°C for 1-5 h.

9. The preparation method according to claim 6 or 7, characterized in that: In step S4, the deformation of a single pass of the cold rolling process is 5-10%, and the total deformation is 75-95%; and / or in step S5, the alloy cold-rolled sheet obtained in step S4 is subjected to a heat treatment at 650-800°C for 1-5 h.

Citation Information

Patent Citations

  • Light refractory high-entropy alloy and preparing method thereof

    CN108300926A

  • Lightweight high-entropy alloy with high strength and high plasticity and preparation method thereof

    CN109402482A